Duodenal microbiota dysbiosis in functional dyspepsia and its potential role of the duodenal microbiota in gut–brain axis interaction: a systematic review - Zhang, Xueping; Chen, Lei; Zhang, Tao; Gabo, Ryu; Wang, Qianying; Zhong, Zhuotai; Yao, Mengxi; Wei, Wei; Su, Xiaolan (Frontiers in Microbiology, 2024)
Background and aims Functional dyspepsia (FD) is a common gastrointestinal disorder associated with brain–gut interaction disturbances. In recent years, accumulating evidence points to the duodenum as a key integrator in dyspepsia symptom generation. Investigations into the pathological changes in the duodenum of FD patients have begun to focus on the role of duodenal microbiota dysbiosis. This review summarizes duodenal microbiota changes in FD patients and explores their relationship with gut-brain interaction dysregulation. Methods Ten databases, including PubMed, MEDLINE, and the Cochrane Library, were searched from inception to 10th October 2023 for clinical interventional and observational studies comparing the duodenal microbiota of FD patients with controls. We extracted and qualitatively summarized the alpha diversity, beta diversity, microbiota composition, and dysbiosis-related factors. Results A total of nine studies, consisting of 391 FD patients and 132 non-FD controls, were included. The findings reveal that the alpha diversity of the duodenal microbiota in FD patients does not exhibit a significant difference compared to non-FD controls, although an upward trend is observed. Furthermore, alterations in the duodenal microbiota of FD patients are associated with the symptom burden, which, in turn, impacts their quality of life. In FD patients, a considerable number of duodenal microbiota demonstrate a marked ascending trend in relative abundance, including taxa such as the phylum Fusobacteria, the genera Alloprevotella, Corynebacterium, Peptostreptococcus, Staphylococcus, Clostridium, and Streptococcus. A more pronounced declining trend is observed in the populations of the genera Actinomyces, Gemella, Haemophilus, Megasphaera, Mogibacterium, and Selenomonas within FD patients. A negative correlation in the relative abundance changes between Streptococcus and Prevotella is identified, which correlates with the severity of symptom burden in FD patients. Moreover, the alterations in specific microbial communities in FD patients and their potential interactions with the gut–brain axis merit significant attention. Conclusion Microbial dysbiosis in FD patients is linked to the onset and exacerbation of symptoms and is related to the disorder of gut–brain interaction. Larger-scale, higher-quality studies, along with comprehensive meta-omics research, are essential to further elucidate the characteristics of the duodenal microbiota in FD patients and its role in FD pathogenesis. Systematic review registration: CRD42023470279, URL: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023470279.